2019
DOI: 10.1021/acs.jafc.9b00446
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Supplementation Increases Reproduction Performance, Milk Yield, and Milk Composition in Lactating Sows and Growth Performance of Their Piglets

Abstract: Tryptophan (Trp) can produce bioactive compounds for appetite regulation, calcium mobilization, and mammary gland homeostasis via a serotonin pathway. This study evaluated the effects of Trp supplementation on the reproduction performance, milk yield, and composition of lactating sows, growth performance of their piglets, and the secretion function of porcine mammary epithelial cells (PMECs). The infrared emulsion analyzer and ELISA analyses revealed that feeding sows with a 0.12% Trp addition increased (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
(96 reference statements)
1
25
0
Order By: Relevance
“…Insufficient feed intake during lactation resulted in a decrease in the provision of nutrients for milk production, which could limit the growth and development of piglets ( Zijlstra et al., 1996 ; Kim et al., 2004 ). It has been reported that flavor compounds as palatability enhancers and feed attractants increase the feed intake of the sow, which is correlated with increased milk production as previously described ( Strathe et al., 2017 ), and support piglet growth ( Laws et al., 2018 ; Miao et al., 2019 ). In the current study, flavor supplementation at a level of 0.1% in the maternal diet increased the average daily feed intake of the sow, litter weight gain, and average daily gain of the piglet.…”
Section: Discussionmentioning
confidence: 59%
“…Insufficient feed intake during lactation resulted in a decrease in the provision of nutrients for milk production, which could limit the growth and development of piglets ( Zijlstra et al., 1996 ; Kim et al., 2004 ). It has been reported that flavor compounds as palatability enhancers and feed attractants increase the feed intake of the sow, which is correlated with increased milk production as previously described ( Strathe et al., 2017 ), and support piglet growth ( Laws et al., 2018 ; Miao et al., 2019 ). In the current study, flavor supplementation at a level of 0.1% in the maternal diet increased the average daily feed intake of the sow, litter weight gain, and average daily gain of the piglet.…”
Section: Discussionmentioning
confidence: 59%
“…A daily examination was carried out in all piglets, especially for fecal appearance on rectal swabs. No faeces present (the rectal swab was dry and clean), watery, liquid, creamy and firm or solid (solid bulbs on the rectal swab) were 6 categories during each evaluation ( Che et al., 2016 ; Miao et al, 2019 ). A piglet was defined as diarrhoeic when those had watery or liquid consistency of faeces on a special day ( Adams et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Amounting studies have been performed to explore the effects of dietary supplementation and reduction of Trp on appetite control, whereas the results are inconsistent and contradictory. For example, animal studies showed that Trp administration can stimulate food intake by enhancing ghrelin, 5-HT, neuropeptide Y (NPY), and the pituitary growth hormone-insulin-like growth factor (GH-IGF) signaling [112,113]. However, intragastric or intraduodenal Trp dose dependently inhibits appetite and promotes the production of CCK, GLP-1, and PYY in the healthy men, whereas failed to affect appetite in the obese men [114][115][116].…”
Section: Tryptophan (Trp)mentioning
confidence: 99%